2019
DOI: 10.1007/s12034-019-1914-1
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of bone repair of rabbit tibia defects induced by scaffolds of $$\hbox {P(VDF-TrFE)/BaTiO}_{3}$$ composites

Abstract: In this work, scaffolds made of a novel experimental 0-3 type composite were implanted onto non-critical defects in rabbit tibiae. This work discusses the bone repair promoted by polyvinylidene fluoride-trifluoroethylene P(VDF-TrFE)/barium titanate (BaTiO 3) composite that scaffolds with 10 vol% BaTiO 3. Prior to implant surgery, the P(VDF-TrFE)/BaTiO 3 scaffolds, moulded into a membrane disk, were subjected to a cytotoxicity test (ASTM F895-84). A standardized transverse osteotomy was made with the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…According to previous works related to the evaluation of biocompatibility of P(VDF-TrFE)BaTiO 3 membranes developed by the research group led by Professor Gimenes, the surface of P(VDF-TrFE)BaTiO 3 was shown to be osteogenic. Supported by published findings [28,34], we assume that Ti-30Ta coated with P(VDF-TrFE)/BaTiO 3 film can provide an osteogenic surface.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…According to previous works related to the evaluation of biocompatibility of P(VDF-TrFE)BaTiO 3 membranes developed by the research group led by Professor Gimenes, the surface of P(VDF-TrFE)BaTiO 3 was shown to be osteogenic. Supported by published findings [28,34], we assume that Ti-30Ta coated with P(VDF-TrFE)/BaTiO 3 film can provide an osteogenic surface.…”
Section: Introductionsupporting
confidence: 75%
“…In addition, this ceramic material presents higher piezoelectricity than PVDF [30,31]. In this context, the combination of BaTiO 3 with a copolymer creates a composite P(VDF-TrFE)/BaTiO 3, which has electrical characteristics that promote bone regeneration [27,[32][33][34]. Considering these benefits and possible solutions, the purpose of the present study was to develop a low-cost methodology to coat Ti-30Ta alloys using P(VDF-TrFE)/BaTiO 3 films by employing a spray coating technique at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The periosteum was repositioned followed by wound suturing, Fig. 3 [ 22 ]. Rabbits were given 0.2 ml of penicillin subcutaneously and ketoprofen (3 mg/kg body weight) intramuscularly for 5 days post-surgery (Eipico pharma, Egypt).…”
Section: Methodsmentioning
confidence: 99%
“…To enhance its ferroelectric and piezoelectric attributes, researchers (Nunes-Pereira et al, 2015) introduced the trifluoroethylene monomer (TrFE) into PVDF, resulting in the copolymer Poly(vinylidene fluoridetrifluoroethylene) (P(VDF-TrFE)), which exhibit improved charge accumulation and storage capabilities, enabling the acquisition of a permanent surface potential. P(VDF-TrFE) is capable of carrying surface charge and has been demonstrated to promote osteogenesis in MSCs in vitro (Luo et al, 2022;Zhang et al, 2022), enhance bone repair in vivo (Gimenes et al, 2019;Zhang et al, 2022), and facilitate macrophage polarization (Dai et al, 2021). The application of an external power source through ITO planar microelectrodes can impart a continuous electrical stimulation to cells or tissues, thereby influencing their morphology and function.…”
Section: Introductionmentioning
confidence: 99%
“…P(VDF-TrFE) is capable of carrying surface charge and has been demonstrated to promote osteogenesis in MSCs in vitro ( Luo et al, 2022 ; Zhang et al, 2022 ), enhance bone repair in vivo ( Gimenes et al, 2019 ; Zhang et al, 2022 ), and facilitate macrophage polarization ( Dai et al, 2021 ). The application of an external power source through ITO planar microelectrodes can impart a continuous electrical stimulation to cells or tissues, thereby influencing their morphology and function.…”
Section: Introductionmentioning
confidence: 99%